Corporate venture capital investments: features and successful practices - V. G. Zinov; O. A. Yeremchenko (Ekonomika Nauki)
The review of domestic and foreign publications presents successful practices of corporate venture investment, which allow to clarify sustainability criteria and requirements for achieving stable functioning of corporate funds. It is shown that the coherence of the fund’s goals with the goals of the parent company, continuity of operation, continuity in relation to strategy, investment focus and the main team, as well as financial stability, which allows us to be a stable partner to portfolio companies throughout their entire life cycle, are of fundamental importance. It is emphasized that corporate venture investments are not an instrument of financial speculation, and the parent company needs the created venture fund, first, as an instrument for search, development, transfer of technologies, products and customers. The main differences between corporate and so-called independent venture capital funds, reflecting various goals, areas of activity, sources of financing, legal status, management remuneration systems and accountability, are examined.